Weight Stigma and Disease and Disability Concepts of Obesity: A Survey of the German Population - Anja Hilbert; Markus Zenger; Claudia Luck-Sikorski; Elmar Brähler (Obesity Facts, 2021)
Introduction: Recent years have witnessed a medicalization of obesity, promoting a classification as a disease or disability in order to reduce or protect against weight stigma and discrimination. This study sought to investigate the public understanding of the disability and disease concepts in obesity, their acceptance, and association with weight stigma. Methods: In a representative German population sample (n = 2,524), public views of obesity as a disease or disability were assessed via a self-report questionnaire. For the assessment of weight stigma, the Weight Control/Blame subscale from the Antifat Attitudes Test was used. Results: A significantly greater acceptance of the disease than the disability concept was found (37.1 vs. 15.4%). Both disease and disability were mainly viewed as physical conditions, although one-third also viewed obesity as a mental disease. While agreement with the disease concept – especially of physical and genetic disease – significantly predicted lower weight stigma; agreement with the disability concept – especially of mental or intellectual disability – predicted higher weight stigma. Conclusions: These results suggest a careful use of the disease and disability terms and precise definitions. The disability concept in particular carries notions that are publicly devalued.